Analisis Faktor Kesiapan Pemberian ASI Eksklusif pada Primigravida - Dinda Putrie Wahyuni; Sri Wahyuni; Apriliani Yulianti Wuriningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Readiness for exclusive breastfeeding was important in supporting the development of newborns. Mrs. Priigravida does not know what influences the relationship in the readiness of exclusive breastfeeding. The purpose of this study is to find out the factors that affect the readiness to give exclusive breastfeeding to primigravida. This study uses a quantitative research method with a cross-sectional approach. The sample used was primigravida pregnant women in the Bangetayu Health Center working area of Semarang City. The number of respondents in this study was 50 people, with the technique used being total sampling. The data obtained were processed statistically using the spearmen rank correlation test. The results showed that the majority of respondents at the age of not at risk were 90%, the last education of high school/vocational school was 56%, mothers who were not working were 60%, knowledge of primigravida was high as 100%, family support was good as 98%, nutritional status of primigravida was high as 96%, and spiritual support of primigravida was high by 100%. The results of the statistical test obtained that the factor that most affects the readiness of exclusive breastfeeding in primigravida is spiritual support with a beta score of 0.582. There was a relationship between knowledge, family support, nutriall status, and spiritual support to readiness of exclusive breastfeeding in primigravida. The most powerful factor of influence is spiritual support.